2022
DOI: 10.1186/s40337-022-00688-6
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical binge eating symptoms in early adolescence and its preceding and concurrent factors: a population-based study

Abstract: Objective Binge eating, loss of control eating and overeating often develop during late childhood or early adolescence. Understanding the presentation of binge eating as early as symptoms manifest and its preceding and concurrent factors is essential to hamper the development of eating disorders. This study examined the prevalence, concurrent and preceding factors (e.g. compensatory behaviors, emotional and behavioral problems) of subclinical binge eating symptoms in early adolescence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Both types of episodes are characterized by a sense of loss of control and the perception that the eating episode is large. Because considerable data suggest that the most salient aspect of binge-eating episodes is the sense of LOC over eating [ 51 53 ], not objective episode size, we examined the frequencies of both OBEs and SBEs in the past 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…Both types of episodes are characterized by a sense of loss of control and the perception that the eating episode is large. Because considerable data suggest that the most salient aspect of binge-eating episodes is the sense of LOC over eating [ 51 53 ], not objective episode size, we examined the frequencies of both OBEs and SBEs in the past 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…A study of 10- to 11-year old children from the ABCD Study, a large, diverse, population-based sample, estimated the prevalence of BED to be 1.1% [ 30 ]. In addition, a population-based study of 14 year old early adolescents found a 14% prevalence rate of subclinical binge-eating behaviors [ 31 ]. Second, early adolescents experience racism and discrimination at unacceptable rates; a recent study estimated that 4.8% of 10- to 11- year old children reported being treated unfairly because of their race, ethnicity or color, and 10% of Black children reported experiencing racism [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a population-based study showed that 452 (12.6%) young adolescents reported subclinical binge eating symptoms. Those who reported loss of eating control and binge eating exhibited compensatory primary behaviors (e.g., hiding or throwing away food, skipping meals) (Derks et al, 2022). About 13% of adolescents in the general population reported at least one episode of binge eating each week (Bentley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%